2014
DOI: 10.1080/10410236.2014.889063
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Autism in Leading Newspapers in China: A Content Analysis

Abstract: The public's lack of understanding and the public's misconceptions about autism in China contribute to the underdiagnosis and undertreatment of the disorder and the stigma associated with it. Mass media are the primary channel through which people learn about autism. This article examines how leading newspapers in China covered autism in the 10-year period of 2003 through 2012 through a framing analysis. It finds that while autism has received increased media attention, it is increasingly framed as a family pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 26 publications
3
63
0
3
Order By: Relevance
“…Minority children on the autism spectrum tend to be diagnosed later, are more frequently misdiagnosed, and receive fewer services and funding (Leigh, Grosse, Cassady, Melnikow, & Hertz‐Picciotto, ; Tek & Landa, ). Stigmatized representations of autism and other disabilities remain common in media consumed by Chinese communities (Bie & Tang, ). In a study of Mandarin‐speaking immigrant parents of children on the autism spectrum, Wang and Casillas () found that parents often employed strategies to protect their families from “losing face” within their communities and to avoid possible rejection and discrimination.…”
Section: Resultsmentioning
confidence: 99%
“…Minority children on the autism spectrum tend to be diagnosed later, are more frequently misdiagnosed, and receive fewer services and funding (Leigh, Grosse, Cassady, Melnikow, & Hertz‐Picciotto, ; Tek & Landa, ). Stigmatized representations of autism and other disabilities remain common in media consumed by Chinese communities (Bie & Tang, ). In a study of Mandarin‐speaking immigrant parents of children on the autism spectrum, Wang and Casillas () found that parents often employed strategies to protect their families from “losing face” within their communities and to avoid possible rejection and discrimination.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of culture, most lay people are exposed to information about ASD via the media [ 52 , 53 ]. It is thus surprising that this information is lacking, as media coverage in China has tended to increase the advocacy for a charity when discussing ASD [ 54 ]. Nonetheless, the total amount of coverage given to ASD in Chinese media is still lacking as compared to that in other geographic regions [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…individual versus government or industry responsibility) (e.g. [31,61,[110][111][112][113][114][115][116][117][118][119]), with studies focusing on obesity being particularly prevalent here (e.g. [26,27,66,75,[120][121][122][123]).…”
Section: Content Of News Mediamentioning
confidence: 99%